UJI DOSIS PUPUK P DAN K TERHADAP PERTUMBUHAN DAN HASIL TANAMAN KEDELAI (Glycine max L. Merril) - David Do Rosario Marques; HARJANTO HARJANTO; TEGUH SUPRIYADI (Fakultas Pertanian, Universitas Tunas Pembangunan Surakarta, 2011)
The study aims to determine the effect of the dosage range of P and K fertilizers on the growth yield of soybean (Glycine max L. Merril) study was conducted in the Green house the Faculty of Agriculture, University of Surakarta Tunas Development The method used is the factorial method with the basic pattern of Randomized Complete Block Design (Block), consisting of two treatment factors, 1) type of dosage P (SP-36) consists of P1 = 25 kg SP-36/ha, P2 = 50 kg SP-36/ha, and P3 = 75 kg SP-36/ha, 2) types of K fertilizer (KCl) is comprised of K1 = 25 kg KCl / ha, K2 = 50 kg KCl / ha, and K3 = 75 kg of KCl / ha, with three times as many replications. The results showed (1) Treatment kinds of fertilizer P (SP-36) showed highly significant at fresh weight of crown, dry weight of crown, pod number per plant, number of empty pods per plant and dry seed weight per plant, but did not affect significantly in plant height. (2) types of K fertilizer treatments (KCl) showed highly significant effect on fresh weight of crown, dry weight of crown, pod number per plant, number of empty pods per plant and dry seed weight per plant, significant effect on plant height, but influential not evident in the number of empty per plant. (3) Interactions between the treatment of types of P fertilizer (SP-36) and K (KCl) have no significant on all parameters. (4) of dry seed weight per plant combined treatment with the highest dose of SP-36 amounted to 75 kg / ha with a dose of KCl at 75 kg / ha (P3K3), was 25,2 g per plant (6,3 ton/ha), and lowest in the combined treatment doses of SP-36 for 25 kg / ha KCl dose of 25 kg / ha (P1K1), was 21,0 g per plant (5,3 Â ton/ha)